THE ROLE OF TEACHER OF SOCIOLOGY SUBJECT IN NURTURING STUDENTâ€™S STUDY GROUPS AT SMAN-1 PALANGKA RAYA - Hermanto, Sogi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this research is to know: the role of teacher of Sociology subject in nurturing studentâ€™s study groups at SMAN-1 Palangka Raya. Population data source, and sample is studentâ€™s study groups at SMAN-1 Palangka Raya where the number of population is 298 students and the sample taken is 25% from the population which is 77 students. The method of the research is by using Descriptive Quantitative Research with a consideration that the problem being observed is still on going and to disclose real and actual problems nowadays. The results descriptively: â€œthe role of teacher of Sociology subject in nurturing studentâ€™s study groups at SMAN-1 Palangka Rayaâ€™, can be concluded that the sample of 77 students shows that from 29 questions in a form of questionnaire who response excellence (84,01%), good (1,16%), fair (14,29%), and poor (0,09%). From the result analysis above it is found that the highest percentage â€œexcellenceâ€ (84,01%) shows that the role of teacher of Sociology subject in nurturing studentâ€™s study group at SMAN-1 Palangka Raya is performed excellence.